Approximate Analytical Solution to a Pore Network Model of Deactivation of Immobilized Glucose Isomerase in Packed-Bed Reactors Using Akbari-Ganji’s Method - Seethalakshmi, B.; Ananthaswamy, V.; Narmatha, S.; Shirly, P. Felicia (Communications in Mathematics and Applications, 2022)
The main objective of this paper is to derive an approximate analytical solution for the mathematical model pertaining to deactivation of immobilized glucose in packed-bed reactors. The Akbari-Ganji’s method is applied to solve the previously developed mathematical model. The approximate analytical expressions corresponding to the concentration and current in the steady state condition have been derived for all values of parameters. Excellent agreement is obtained between the analytical solution and the numerical simulation. The analytical solution presented in this paper is presented for the first time. The results of this work will provide a better understanding of the mathematical model examined.